Comparison of habitual visual acuity and stereoacuity between children attending KEMAS and urban private preschools - Naufal N,; Sharanjeet Kaur,; Narayanasamy S,; Ahmad M,; Kadar M,; Mohd Ali M,; Mohd Izzuddin Hairol, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
The assessment of a preschooler’s visual status is important as it forms part of the measure to assess the child’s school readiness. However, not all children attending preschools have equal opportunity to undergo vision screening programmes. In this study, we measured presenting habitual near and distance visual acuity and stereoacuity in 6-year-old children (n=385). These parameters were measured in and compared between preschoolers attending urban, privately-run kindergartens and those attending KEMAS preschools, which were typically from suburban and rural areas with families of very low income. Seven percent of KEMAS preschoolers failed the distance visual acuity test while the failure rate for private preschoolers was 6.0%. For near visual acuity, a higher percentage of private preschoolers failed the test (8.7%) than KEMAS preschoolers (4.9%). A slightly higher percentage of private preschoolers had weak stereopsis (3.3%) compared to KEMAS preschoolers (2.5%). However, the differences found between the two preschooler groups were not statistically significant (all p>0.05). The proportion of children who failed each of the screening criteria for distance vision, near vision, and stereopsis was similar between KEMAS and private preschools. Therefore, an universally inclusive vision screening programme should be conducted for all preschool types to detect, diagnose, treat, and potentially prevent any visual impairment.